Mewujudkan Generasi Cerdas: Implementasi Kampus Mengajar untuk Peningkatan Literasi, Numerasi, dan Digitalisasi di SMPN 3 Gerung - Nur Asmita Purnamasari; Ni Ketut Anggriani; Ahmad Sahnan; Ari Wardana; Hulfiana Hulfiana; Nauval Waraqoh Dwinata (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The Kampus Mengajar Program is an initiative by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) aimed at improving the quality of education in Indonesia, particularly in schools facing challenges in literacy, numeracy, and digitalization. SMPN 3 Gerung is one of the target schools of the Kampus Mengajar Batch 7 Program, where issues such as low reading interest, lack of understanding of numeracy concepts, and limited use of technology in learning were identified.The objective of this community engagement is to enhance students’ literacy, numeracy, and digital adaptation skills through various intervention programs designed and implemented by Kampus Mengajar students. The method employed includes school needs assessment, solution-based program design, phased implementation, and evaluation to measure program effectiveness. The literacy program consists of 15-minute reading sessions before lessons, a reading corner, and a literacy clinic. The numeracy program includes a numeracy-rich environment and educational games such as the snake and ladder game and puzzles. Meanwhile, the digital adaptation program encompasses Canva training and the use of digital educational media.The results of this program indicate an improvement in students’ literacy and numeracy skills, as evidenced by increased pre-test and post-test scores. Additionally, students' ability to utilize technology for learning has significantly improved. Thus, this program has positively contributed to enhancing the quality of education at SMPN 3 Gerung and can serve as a model for similar community engagement initiatives in other schools facing comparable challenges.